Microstructure and properties of jet pulse electrodeposited Ni-TiN nanocoatings - Li, Qiang (2022)
The current work investigates the successful preparation of Ni-TiN coatings via the jet electrodeposition method. The x-ray diffraction, high-resolution transmission electron microscopy, electrochemical workstation, and triboindenter were used to analyze the structure, mechanical deformation response, and corrosion properties of the coatings. The results reveal that the Ni-TiN coating produced by the deposition method had a fine and uniform microstructure at a 5 g/L concentration of TiN. The mean sizes of TiN nanoparticles and Ni grains were found to be 23.3 and 43.9 nm, respectively. The corrosion potential of the Ni-based TiN coating obtained at 5 g/L by electrodeposition was as minimum as − 0.396 V with a corrosion current density of 1.06 × 10−3 mA/cm2. The Ni-TiN coatings prepared, respectively, at three different concentrations (3, 5, and 8 g/L) under the applied load of 1500 µN were about 34.9, 28.2, and 30.3 µm in vertical depth, respectively. The coatings obtained at 5 g/L had the maximum nanohardness of 34.5 GPa when compared to the other coatings. In addition, the coatings were then subjected to three sliding scans, and the Ni-TiN coating prepared at 5 g/L showed the least magnitude of wear damage and plastic deformation when compared to the other coatings.